Pelatihan dan Pendampingan Inovasi Produk Tempe Pemberdayaan Menuju UMKM Modern - Muhammad Asnawi; Suardi Suardi; Indah Clara Sari; Sri Wahyuni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The tempe UMKM partnering with this program still use rudimentary production equipment, limiting product capacity and quality, making it difficult to meet modern market standards. These limitations result in minimal product innovation, unattractive packaging and low market penetration, particularly in the digital realm. To address these challenges, training and mentoring focused on improving production skills, innovating tempe variants and developing modern packaging. The implementation method included technical training on hygienic and innovative tempe production, a packaging design workshop that meets food safety standards, social media-based digital marketing training and business management mentoring and progress monitoring for three months. The results showed that partners were able to produce innovative tempe products with more attractive packaging, utilize digital platforms for marketing and increase turnover by an average of 20-30% during the mentoring period. The conclusion of this activity is that integrated training and mentoring, even starting with simple equipment, can encourage the transformation of tempe UMKM to become more modern, adaptive and competitive in the market